Corrosion of Steels in Water and Hydrogen Sulphide - A, Adebayo; B. S, Oluwadare (Review of Industrial Engineering Letters, 2014)
The importance of carbon steel in the petroleum industries cannot be over emphasized. The carbon steel is susceptible to internal corrosion due to H2S/CO2 environment. The two gasses, in combination with water, defines most of the corrosion problems in the oil and gas production. This research paper is aimed at investigating the corrosion rate of steels in water and H2S. Eight steel samples (AISI 301, AISI 302, AISI 304, AISI 304L, AISI 308, AISI 309, St 35 and St 37) were used for the experiment. The results obtained showed that the corrosion rate in water saturated H2S was higher as compared to wet and dry H2S gases. This was attributed to the aqueous state of water saturated H2S, which increases the rate of ion dissociation. The high rate of ion dissociation increases the rate of ion penetration into the steel (diffusion rate) and thus the corrosion rate.